2016
DOI: 10.3109/1354750x.2016.1171901
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of glial fibrillary acidic protein and Nogo-A in children with autism spectrum disorders

Abstract: It will be of great interest to determine other potential causes of elevated serum levels of GFAP, and whether this elevation has any phenotypic effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…To our knowledge this is the first analysis to report the presence of serum levels of GFAP in ASD and typical development children in Chinese population. Inconsistent with the results of our research, a previous study finished by Cetin et al (2016) found that the mean serum levels of GFAP were significantly lower in ASD than controls (141.7 pg/ml VS. 428.5 pg/ml). Furthermore, Kirkman et al (2008) reported that there was no significant difference of GFAP between autism and controls.…”
Section: Discussionsupporting
confidence: 87%
“…To our knowledge this is the first analysis to report the presence of serum levels of GFAP in ASD and typical development children in Chinese population. Inconsistent with the results of our research, a previous study finished by Cetin et al (2016) found that the mean serum levels of GFAP were significantly lower in ASD than controls (141.7 pg/ml VS. 428.5 pg/ml). Furthermore, Kirkman et al (2008) reported that there was no significant difference of GFAP between autism and controls.…”
Section: Discussionsupporting
confidence: 87%
“…GFAP serum levels have been assessed in a study by Çetin et al (Cetin et al, 2016). According to this study, serum GFAP levels in ASD patients were lower compared to a healthy control group.…”
Section: Discussionmentioning
confidence: 99%
“…Body fluids are easy to collect, and their analysis is less expensive compared to neuroimaging and genome studies. Recent studies show that blood samples are one of the most promising targets to search for characteristic biomarkers for ASD, not only due to their easy accessibility but also because of their important biological information content on the health status of children with this disorder [1,4,[9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%